High-speed wide-field photoacoustic microscopy using a cylindrically focused transparent high-frequency ultrasound transducer - Maomao Chen; Laiming Jiang; Clare Cook; Yushun Zeng; Tri Vu; Ruimin Chen; Gengxi Lu; Wei Yang; Ulrike Hoffmann; Qifa Zhou; Junjie Yao (Photoacoustics, 2022)
Combining focused optical excitation and high-frequency ultrasound detection, optical-resolution photoacoustic microscopy (OR-PAM) can provide micrometer-level spatial resolution with millimeter-level penetration depth and has been employed in a variety of biomedical applications. However, it remains a challenge for OR-PAM to achieve a high imaging speed and a large field of view at the same time. In this work, we report a new approach to implement high-speed wide-field OR-PAM, using a cylindrically-focused transparent ultrasound transducer (CFT-UT). The CFT-UT is made of transparent lithium niobate coated with indium-tin-oxide as electrodes. A transparent cylindrical lens is attached to the transducer surface to provide an acoustic focal line with a length of 9 mm. The excitation light can pass directly through the CFT-UT from the above and thus enables a reflection imaging mode. High-speed imaging is achieved by fast optical scanning of the focused excitation light along the CFT-UT focal line. With the confocal alignment of the optical excitation and acoustic detection, a relatively high detection sensitivity is maintained over the entire scanning range. The CFT-UT-based OR-PAM system has achieved a cross-sectional frame rate of 500 Hz over the scanning range of 9 mm. We have characterized the system’s performance on phantoms and demonstrated its application on small animal models in vivo. We expect the new CFT-UT-based OR-PAM will find matched biomedical applications that need high imaging speed over a large field of view.